Brain activity changes in a macaque model of oxaliplatin-induced neuropathic cold hypersensitivity - Nagasaka, Kazuaki (Sci Rep, 2017)
The antineoplastic agent oxaliplatin induces a painful peripheral neuropathy characterized by an acute cold hypersensitivity. There is a lack of effective treatments to manage oxaliplatin-induced cold hypersensitivity which is due, in part, to a lack of understanding of the pathophysiology of oxaliplatin-induced cold hypersensitivity. Thus, brain activity in oxaliplatin-treated macaques was examined using functional magnetic resonance imaging (fMRI). Oxaliplatin treatment reduced tail withdrawal latency to a cold (10 °C) stimulus, indicating cold hypersensitivity and increased activation in the secondary somatosensory cortex (SII) and the anterior insular cortex (Ins) was observed. By contrast, no activation was observed in these areas following cold stimulation in untreated macaques. Systemic treatment with an antinociceptive dose of the serotonergic-noradrenergic reuptake inhibitor duloxetine decreased SII and Ins activity. Pharmacological inactivation of SII and Ins activity by microinjection of the GABA(A) receptor agonist muscimol increased tail withdrawal latency. The current findings indicate that SII/Ins activity is a potential mediator of oxaliplatin-induced cold hypersensitivity.